Mitigating Moral Distress in Leaders of Healthcare Organizations: A Scoping Review. Issue 5 (September 2022) - Hertelendy, Attila J.; Gutberg, Jennifer; Mitchell, Cheryl; Gustavsson, Martina; Rapp, Devin; Mayo, Michael; von Schreeb, Johan
Abstract : Goal: Moral distress literature is firmly rooted in the nursing and clinician experience, with a paucity of literature that considers the extent to which moral distress affects clinical and administrative healthcare leaders. Moreover, the little evidence that has been collected on this phenomenon has not been systematically mapped to identify key areas for both theoretical and practical elaboration. We conducted a scoping review to frame our understanding of this largely unexplored dynamic of moral distress and better situate our existing knowledge of moral distress and leadership. Methods: Using moral distress theory as our conceptual framework, we evaluated recent literature on moral distress and leadership to understand how prior studies have conceptualized the effects of moral distress. Our search yielded 1, 640 total abstracts. Further screening with the PRISMA process resulted in 72 included articles. Principal Findings: Our scoping review found that leaders—not just their employees— personally experience moral distress. In addition, we identified an important role for leaders and organizations in addressing the theoretical conceptualization and practical effects of moral distress. Practical Applications: Although moral distress is unlikely to ever be eliminated, the literature in this review points to a singular need for organizational responses that are intended to intervene at the level of the organization itself, not just at the individual level. Best practices require creating stronger organizational cultures that are designed to mitigate moral distress. This can be achieved through transparency and alignment of personal, professional, and organizational values.